2020
DOI: 10.1126/science.abb0979
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond spectroscopy of liquid water

Abstract: Electronic dynamics in liquids are of fundamental importance, but time-resolved experiments have so far remained limited to the femtosecond time scale. We report the extension of attosecond spectroscopy to the liquid phase. We measured time delays of 50 to 70 attoseconds between the photoemission from liquid water and that from gaseous water at photon energies of 21.7 to 31.0 electron volts. These photoemission delays can be decomposed into a photoionization delay sensitive to the local environment and a delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 59 publications
1
66
0
Order By: Relevance
“…However, Figure 3b displays very clearly that the subsequent ionization process nl + ω → E(l ± 1) favors very strongly the nd intermediate states and the ns states can be safely ignored in uRABBITT. We see from the same Figure 3b that the photoionization cross-sections σ nd depend rather weakly on n, and it is the oscillator strength factor f 1/2 nd that determines largely the resonant amplitude (6) in Ne.…”
Section: Target Electronic Structurementioning
confidence: 64%
See 2 more Smart Citations
“…However, Figure 3b displays very clearly that the subsequent ionization process nl + ω → E(l ± 1) favors very strongly the nd intermediate states and the ns states can be safely ignored in uRABBITT. We see from the same Figure 3b that the photoionization cross-sections σ nd depend rather weakly on n, and it is the oscillator strength factor f 1/2 nd that determines largely the resonant amplitude (6) in Ne.…”
Section: Target Electronic Structurementioning
confidence: 64%
“…We use the software package ATOM [23] to peform the calculations of the quantities E nl , f nl , and σ nl entering Equation (6). These results are presented in Table 1 and displayed graphically in Figure 3.…”
Section: Target Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Both techniques have been applied to a wide range of attosecond time-resolved photoelectron emission dynamics in atoms [6][7][8] , molecules [9][10][11] and even condensed matters [12][13][14][15] . Studies have demonstrated the photoelectron emission time delays arising from different ionization shells [16][17][18] , shape resonances 9,10,19 , electron correlation 20 , orbital asymmetry 21 , spatial asymmetry (chirality) 11 , and electron delocalization 22 .…”
Section: Introductionmentioning
confidence: 99%
“…But how fast electronic relaxation really is has remained elusive in many molecular systems, owing to experimental limitations, particularly temporal resolution. This situation has changed with the advent of attosecond science that has redefined the frontiers of time-resolved measurements on molecules (7)(8)(9)(10)(11)(12)(13)(14). Attosecond transient-absorption spectroscopy (ATAS) is a particularly powerful technique for accessing both electronic and structural dynamics (15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%